October Show. - Keziere, Russell; MacWilliam, David (Vancouver : Vancouver Art Gallery, 1983)
Anderson, John ; Arden, Roy ; Average, Joe ; Balkind, Alvin ; Banana, Anna ; Penner Bancroft, Marian ; Beer, Ruth ; Birstein, Suzy ; Bissett, Bill ; Bradley, Randy ; Brett, Leonard ; Bridge, Jim ; Bull, Hank ; Buquet, Jack ; Buriak, Myros ; Butler, Margot ; Carrico, Jim ; Carter, Linda ; etc.
October Show, 1078 Hamilton Street, Vancouver, October 15 - 29, 1983
English
kunstcatalogus